Risks of arsenic-contaminated fish consumption in Manado: Intervention implications from an environmental health risk assessment - Maddusa, Sri Seprianto; Asrifuddin, Afnal; Mantjoro , Eva M. (Sociality: Journal of Public Health Service, 2025)
Heavy metal contamination in coastal ecosystems continues to be a critical yet under-addressed public health issue, particularly in developing countries where environmental monitoring and risk communication remain limited. Previous studies have insufficiently linked seafood-borne arsenic exposure with targeted health interventions for coastal populations. This study aimed to assess public health risks associated with arsenic (As) exposure from fish and shellfish consumption in Manado Bay, Indonesia, using an Environmental Health Risk Assessment (EHRA) approach. Conducted from April to October 2025, this cross-sectional study combined laboratory analysis of seafood samples with exposure assessment among 50 coastal residents selected via cluster sampling. The highest arsenic concentration was identified in Yellowstripe Red Snapper (Lutjanus kasmira) at 1.61 mg/kg, exceeding FAO/WHO safety thresholds. The estimated daily intake and risk quotient (RQ) for L. kasmira consumption surpassed the reference dose, with an average RQ of 4.92 over a 30-year exposure duration, indicating significant chronic health risks. These findings underscore the urgent need for integrated public health interventions, including consumption advisories, environmental risk communication, seafood safety regulations, and pollution mitigation strategies. Addressing these gaps is critical to protect vulnerable populations and inform policy actions for sustainable coastal health management in Indonesia and similar settings.